LEARNERS’ PERSPECTIVES ON TRADITIONAL CLASSROOM VERSUS ONLINE LEARNING TOWARDS ACADEMIC PERFORMANCE - Nazratul Aini Ramli; Razifa Mohd Razlan; Raja Mariam Raja Baniamin (Journal of Islamic, Social, Economics and Development, 2024)
Over the years, tertiary education has argued the effects of traditional classroom instruction versus online learning. This study emphasises the perspectives of two methods which are traditional classroom and online learning among the learners based on a comprehensive review of the past literature. All the perspectives are the elements that may affect the learners' academic performance as it is the outcome of the learning process. Some learners stated their gratitude and inclinations for the online learning environment, which gives them more exposure and flexibility to technology. While others who inclined traditional classroom learning considered social interaction and participation to develop a sense of community is crucial. Despite their different perspectives on the two methods, the significance of these outcomes in learners' academic performances was commonly similar. On the other hand, there was a slight difference in academic performance in English language learning where the learners performed effectively in online learning as compared to traditional classroom learning. Thus, this study can give some insights to educators in designing their teaching approaches. Aside from that, it also can establish the imperative points in learning process without lessening the quality in traditional classroom and avoid fully dependence on technology.